2013
DOI: 10.1016/j.ijgo.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of, attitudes toward, and barriers to the practice of emergency contraception among women in Sikkim, India

Abstract: Knowledge and practice of EC was low among the women interviewed. There is a need for intensive information EC on the available methods and their correct timing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
2
8
0
3
Order By: Relevance
“…Furthermore, the tendency of women to use withdrawal would be higher if they had an intention to have more children. These findings are in line with those of other studies indicating the role of the number of living children in their contraceptive method choice (19,20). Based on the results of the current study, younger women with lower parity are more likely to prefer withdrawal.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the tendency of women to use withdrawal would be higher if they had an intention to have more children. These findings are in line with those of other studies indicating the role of the number of living children in their contraceptive method choice (19,20). Based on the results of the current study, younger women with lower parity are more likely to prefer withdrawal.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies [ 25 , 26 ], the condom was the most well-known contraceptive method by all participants. Emergency contraception could play a critical role in reducing unintended pregnancies [ 26 , 30 , 31 ]; however, many studies found that the awareness and use of emergency contraception was often low among women in India, Latin America and African countries [ 30 - 32 ]. Likewise, our results showed that emergency contraception pills were not known by most of the participants as a method for preventing pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Sumber informasi terkait kontrasepsi khususnya kontrasepsi darurat pada wanita di Sikkim, India yang paling umum adalah media elektronik (77,1%), teman atau kerabat (33,8%), dan tenaga kesehatan (30,4%) (17). Teman dan kerabat dari ibu juga menjadi sumber informasi terkait penggunaan alat KB dan mempengaruhi pengambilan keputusan ibu untuk menjadi akseptor KB.…”
Section: Sumber Informasi Tentang Program Kbunclassified